VS2 nanosheet as a promising candidate of recycle and reuse NO2 gas sensor and capturer: a DFT study. (20th April 2021) - Zhao, Rumeng; Wang, Tianxing; An, Yipeng; Dai, Xianqi; Xia, Congxin
Abstract: We describe the utilization of VS2 nanosheet as high sensing response, reuse, and thermodynamic stability at room temperature NO2 and NO gas sensors by using the density functional theory method. We focus on the electronic structures and adsorption energy toward a variety of gaseous molecules (such as O2, CO, H2 O, NH3, NO, and NO2 ) adsorbed on the VS2 nanosheet. The results show that chemical interactions existed between NO/NO2 molecules and VS2 nanosheet due to sizable adsorption energy and strong covalent (S–N) bonds. In particular, the adsorption energies, charge transfer and electronic properties between NO2 adsorbed system is significantly changed compared with the other gas molecules (CO, NO, H2 O, NH3, and O2 ) adsorbed systems under biaxial strains, which is effective to achieve the capture or reversible release of NO2 for cycling capability. Our analysis indicates that VS2 nanosheet is promising as electrical devices candidate for NO2 high-performance gas sensor or capturer.